The efficacy of ultrasound treatment as a reversible male contraceptive in the rhesus monkey - VandeVoort Catherine A; Tollner Theodore L (BMC, 2012)
Abstract Background The use of therapeutic ultrasound as a contraceptive approach has involved nonhuman primates as well as rats and dogs. The current study was undertaken to determine whether this treatment could be a method for reversible contraception, using a model with testes size similar to adult humans. Methods Two methods of ultrasound exposure were used, either the transducer probe at the bottom of a cup filled with saline (Cup) or direct application to the surface of the scrotum (Direct). Four adult rhesus (Macaca mulatta) males with normal semen parameters were treated with therapeutic ultrasound at 2.5 W/cm(2) for 30 min. Treatment was given 3 times, one every other day on a Monday-Wednesday-Friday schedule. For each male, semen quality was evaluated a minimum of three times over several months prior to ultrasound exposure and weekly for two months following ultrasound treatment. Results Semen samples from all males, regardless of exposure method, exhibited a decrease in the percentage of motile sperm following ultrasound treatment. There was an average reduction in motility of 40% the week following treatment. Similarly, curvilinear velocity and the percentage of sperm with a normally shaped flagellum were also reduced in all males following ultrasound treatment. A significant reduction in the total number of sperm in an ejaculate (total sperm count) was only observed in males that received ultrasound via the cup method. Following treatment via the cup method, males exhibited up to a 91.7% decrease in average total sperm count (n = 2). Sperm count did not approach pre-treatment levels until 8 weeks following ultrasound exposure. Conclusions The sustained reduction in sperm count, percent motility, normal morphology, and sperm vigor with the cup exposure method provides proof of principle that testicular treatment with ultrasound can be an effective contraceptive approach in humans.